A real-world risk analysis of biological treatment (adalimumab and etanercept) in a country with a high prevalence of tuberculosis and chronic liver disease: a nationwide population-based study. (4th May 2017) - Chiu, Y-M; Tang, C-H; Hung, S-T; Yang, Y-W; Fang, C-H; Lin, H-Y
Abstract : Objectives : Few studies on tumour necrosis factor (TNF) inhibitor-associated tuberculosis (TB) and hepatic events have been performed in regions where these risks are elevated. This study aimed to provide a direct comparison between adalimumab and etanercept in a high-risk population and to address the implications for physicians working with patients in such an environment. Method : Data collected from the National Health Insurance Research Database (NHIRD) in Taiwan between 2007 and 2011 were analysed retrospectively for incidences of eight adverse events associated with TNF-α inhibitors. Hazard ratios (HRs) of adalimumab vs. etanercept were calculated using a Cox proportional hazards model. Results : During this 5-year period, 86 events of TB were reported after 5317 person-years of exposure to adalimumab (1.62 events per 100 person-years), compared to 44 events after 7690 person-years of exposure to etanercept (0.57 events per 100 person-years). For serious hepatic events that led to hospitalization, 0.75 events were reported per 100 person-years of exposure to adalimumab compared to 0.39 events per 100 person-years of exposure to etanercept. Adjusted HRs for TB [aHR 3.06, 95% confidence interval (CI) 2.09–4.49, p < 0.0001], hospitalization due to a hepatic event (aHR 2.05, 95% CI 1.27–3.30, p = 0.0035), and serious infection (aHR 1.48, 95% CI 1.19–1.84, p = 0.0005) attained significance. Conclusions : TNF-α-targeting therapies with the monoclonal antibody adalimumab confers significant added risk of TB and serious hepatic events compared to therapies with the soluble fusion protein etanercept. Tailored strategies to attenuate these risks are warranted in high-risk regions such as Taiwan.